Disorders of the Blood Coagulation System in Patients with Infectious Endocarditis - Chyzh, Kostiantyn P.; Koltunova, Hanna B. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Infectious endocarditis is a disease which is still hard to diagnose and treat. The success of the proposed ther-apy depends not only on the surgical correction of the heart disease, but also on effective perioperative management of this group of patients. In most cases, patients have a long history of drug treatment and compromised status of all organs and systems. Coagulation disorders in patients with infectious endocarditis are one of the main links which lead to the patient’s death, despite advances in therapeutic and surgical treatment. Since the development of infectious endocarditis is based on thrombo-inflammatory lesions of the endocardium as a result of the interaction of microorganisms and modifiers of the blood coagulation system, the appointment of effective anticoagulant therapy in the postoperative period becomes one of the important tasks in resuscitation. The need to maintain balance between the coagulation and anticoagulation systems of hemostasis requires constant monitoring of the coagulation system and careful administration of anticoagulants. The aim. To demonstrate an example of an alternative scheme of anticoagulant therapy in a patient with postopera-tive gastrointestinal bleeding after cardiac surgery for infectious endocarditis. Materials and methods. We present a clinical case of treatment of acute gastrointestinal bleeding in the early post-operative period in a patient after cardiac surgery for infectious aortic valve endocarditis. The 56-year-old patient K. was taken to the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine by ambulance with a diagnosis: Infectious endocarditis of the aortic and mitral valves. Combined aortic defect with a predominance of insufficiency, mitral regurgitation, tricuspid insufficiency. Pulmonary arterial hypertension. Degree II respiratory failure. Ischemic heart disease: non-Q-wave myocardial infarction (as of October 29, 2020), RCA stenting (November 2, 2020), post-infarction atheroscle-rotic cardiosclerosis. Degree III hypertension, stage 2, risk 4. Heart failure 2B, functional class III. A salvage cardiac surgery was performed: aortic valve replacement. Mitral and tricuspid valve plastics. On day 2 of the postoperative period, against the background of anticoagulant therapy prescribed according to international recommendations, gastrointestinal bleeding developed. Anticoagulant therapy regimen was adjusted. The proposed scheme of hemostasis control allowed to normalize the blood parameters and to avoid blood loss. On day 10 of the postoperative period, standard scheme of anticoagulant ther-apy could be renewed, and the patient was transferred to the therapeutic department under the supervision of cardiologist. Conclusions. The proposed variant of anticoagulant therapy in the postoperative period in a patient operated on for infectious endocarditis created the conditions for normalization of hemostasis. Complete withdrawal of anticoagulants and transfer of patients to a continuous infusion of heparin under the control of APTT with a target value allows not only to control the risk of bleeding, but also to prevent thrombosis.